Valorisation of whey and buttermilk for production of functional beverages : an overview of current possibilities - Barukčić, Irena (Array, 2019)
Whey and buttermilk are the main by-products of the dairy industry, both having excellent nutritional properties. Buttermilk contains a unique component, the milk fat globule membrane (MFGM). MFGM contains bioactive compounds with positive health effects like antitumour or cholesterol-lowering impact. Whey proteins are found in whey and are a source of bioactive peptides acting positively on coronary, gastrointestinal, immune and nervous systems. Yet, buttermilk and whey are insufficiently utilized in functional food production. Various technological solutions have been studied in order to increase the production of foods based on whey and/or buttermilk whereby the production of beverages appear to be most acceptable from the economic and technological point of view. Thus, the aim of this paper is to give an overview of current knowledge about the possibilities of creating whey and/or buttermilk beverages.